2013
DOI: 10.1128/jcm.01531-13
|View full text |Cite
|
Sign up to set email alerts
|

High Similarity of Novel Orthoreovirus Detected in a Child Hospitalized with Acute Gastroenteritis to Mammalian Orthoreoviruses Found in Bats in Europe

Abstract: e Mammalian orthoreoviruses (MRVs) are known to cause mild enteric and respiratory infections in humans. They are widespread and infect a broad spectrum of mammals. We report here the first case of an MRV detected in a child with acute gastroenteritis, which showed the highest similarity to an MRV reported recently in European bats. An examination of a stool sample from the child was negative for most common viral and bacterial pathogens. Reovirus particles were identified by electron microscopic examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 39 publications
0
90
0
1
Order By: Relevance
“…We speculate that bats are the primary hosts for genetic exchange among different MRV strains under natural conditions, as they possess certain ideal characteristics such as long life span, diversity, wide distribution, and they carry a number of zoonotic viruses from many different virus families (Smith and Wang, 2013). The last decade has experienced a surge in reports of MRVs of bat origin that have a significant impact on human and animal health (Hu et al, 2014;Kohl et al, 2012;Steyer et al, 2013b;Wang et al, 2015a). Moreover, the genome of MRV-ZJ2013 shows reassortment among different bat MRV serotypes: M1 and S3 seem to originate from serotype 1 bat MRV; M3 and S2 seem to come from serotype 2 bat MRV; and L2 and S4 come from serotype 3 bat MRV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that bats are the primary hosts for genetic exchange among different MRV strains under natural conditions, as they possess certain ideal characteristics such as long life span, diversity, wide distribution, and they carry a number of zoonotic viruses from many different virus families (Smith and Wang, 2013). The last decade has experienced a surge in reports of MRVs of bat origin that have a significant impact on human and animal health (Hu et al, 2014;Kohl et al, 2012;Steyer et al, 2013b;Wang et al, 2015a). Moreover, the genome of MRV-ZJ2013 shows reassortment among different bat MRV serotypes: M1 and S3 seem to originate from serotype 1 bat MRV; M3 and S2 seem to come from serotype 2 bat MRV; and L2 and S4 come from serotype 3 bat MRV.…”
Section: Discussionmentioning
confidence: 99%
“…MRVs were traditionally believed to be the causative agents of mild respiratory and enteric infections, without significant clinical impact. However, in the last decade, increasing numbers of studies in humans and other mammals have shown that they can cause severe illness in humans and other mammals, including upper respiratory tract infections, encephalitis, and diarrhea (Chua et al, 2008;Ouattara et al, 2011a;Steyer et al, 2013a). MRVs have been isolated from a broad range of mammalian species, including bats (Hu et al, 2014;Kohl et al, 2012;Lelli et al, 2013;Lorusso et al, 2014;Thalmann et al, 2010;Wang et al, 2015a;Yang et al, 2015), civet cats , cows (Anbalagan et al, 2014), mink (Lian et al, 2013), pigs (Dai et al, 2012b;Kwon et al, 2012b;Thimmasandra Narayanappa et al, 2015;Zhang et al, 2011a), dogs (Decaro et al, 2005) and humans (Chua et al, 2008;Ouattara et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap, we have used a sequenceindependent, preamplification-free deep sequencing approach to investigate and compare two different pools of RNA virus sequences from the infected plants: single-stranded RNA (ssRNA) isolated from purified viral particles (VP pool) and vsiRNAs (sRNA pool). Deep sequencing of viral RNA directly from purified viral particles was performed only in a few cases and was shown to be highly efficient for enrichment for viral nucleic acids (4,22,23). Here, we have used the recently developed CIM monolithic chromatography-based approach for fast purification of viral particles (24).…”
mentioning
confidence: 99%
“…Two recent studies have already applied monolith chromatography toward this direction showing that the method alone is efficient in enriching virus particles sample before nucleic acid isolation and next‐generation sequencing application. In one of them, QA monolithic disc and a gradient elution approach were exploited to enrich the fraction of a novel clinical orthoreovirus isolate from a clarified stool sample . This allowed to easily construct the viral genome by using Ion Torrent NGS platform.…”
Section: Sample Enrichment Improving Next Generation Sequencingmentioning
confidence: 99%